ANALISIS MONITORING DAN EVALUASI (MONEV) DALAM IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH (MBS) DI SD NEGERI 12 SESETAN - Ida Bagus Gede Surya Abadi; Chindytia Chindytia; Ni Putu Bintang Pande Cahyani; Nyoman Deby Suastini; Agnestia Arum Agata (STKIP Pesisir Selatan, 2026)
This study aims to analyze the role of monitoring and evaluation in the implementation of School-Based Management (SBM) and its effectiveness in improving the quality of education at SD Negeri 12 Sesetan. This research uses a naturalistic qualitative approach with data collection techniques through interviews, observations, and documentation. The research informants consist of the principal as the main informant, as well as teachers and education staff as supporting informants. The results show that the implementation of SBM has been carried out through planning, implementation, monitoring, and evaluation involving all school members. Monitoring is conducted through principal supervision, regular coordination, and oversight of program implementation, while evaluation is carried out at the end of activities as a basis for program improvement. Monitoring and evaluation contribute to improving the effectiveness of school management, the quality of learning, and student discipline. However, several challenges were still found, including limited facilities, time management issues, and inconsistent implementation of monitoring and evaluation.